Application of shallow seismic reflection in subsurface geological mapping - Umar Hamzah; Abdul Rahim Samsudin (Universiti Kebangsaan Malaysia, 1999)
Shallow seismic reflection is one of the surface geophysical techniques to investigate indirectly subsurface structures within depths of 200 meters. Structures such as faults, sedimentary features, hydrogeological aquifers, depth to bedrock and limestone sinkholes are always related to the geological mapping. This paper presents some of the shallow seismic reflection results in imaging subsurface structures at a few selected localities. The presence of a limestone sinkhole as small as 20 ´ 5 meters was imaged at the old limestone quarry in Batu Caves, Kuala Lumpur. Sedimentary structures, aquifers and thickness of alluvium on granite bedrock were imaged from surveys at Pekan, Pahang and Bacok, Kelantan. Faults have also been detected using the same technique from a survey in Midland, England. Currently a minimum depth obtained is approximately 20 meters and the vertical resolution is approximately 5 meters.